PEMBAGIAN WARISAN DAN PERAN NOTARIS DALAM MASYARAKAT HUKUM ADAT NIAS - Sri Ayu sukmawati Loi; Jeane Neltje Saly (UNES Law Review, 2023)
Customary inheritance law in Indonesia is influenced by the existence of a family system such as in terms of the form of marriage and how to draw lineage to determine who has the right to be the heir and has the right to inherit. The indigenous people of Nias who adhere to an inheritance system based on a patrilineal descent system are generally known as honest marriages, namely marriages that are carried out by paying honestly (BÖwÖ) from the man to the woman. In the inheritance system in the Nias tribal community, the role of men is as the heirs of their parents, while women are not heirs. This study uses an empirical juridical approach. The problem in this research is how the division of inheritance and the role of the Notary in the customary law community of Nias. This research is important to carry out to find out the development of inheritance law and the role of the notary in the customary law community of Nias where there has been development in terms of inheritance of female heirs who have received a share of the inheritance of their parents even though the share is not larger than the male heirs and this is a family policy and agreement